2022
DOI: 10.1111/jocs.16389
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of the Perceval sutureless bioprosthesis for pulmonary valve replacement in high‐risk endocarditis patients: A case series

Abstract: We present the first known cases of successful implantation of the Perceval sutureless bioprosthetic valve in the pulmonary position in two high-risk endocarditis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The use of sutureless valves in infective endocarditis has been previously reported. [1][2][3] Singh et al 4 have reported a single-center successful surgical treatment of two cases using a sutureless bioprosthesis in an infected pulmonary native valve. The implantation of these types of valves in active endocarditis may still be considered a relative contraindication.…”
Section: Valve Repair/replacementmentioning
confidence: 99%
“…The use of sutureless valves in infective endocarditis has been previously reported. [1][2][3] Singh et al 4 have reported a single-center successful surgical treatment of two cases using a sutureless bioprosthesis in an infected pulmonary native valve. The implantation of these types of valves in active endocarditis may still be considered a relative contraindication.…”
Section: Valve Repair/replacementmentioning
confidence: 99%